Sleep Disturbance Partially Mediates the Relationship Between Intimate Partner Violence and Physical/Mental Health in Women and Men. Issue 16 (August 2017) - Lalley-Chareczko, Linden; Segal, Andrea; Perlis, Michael L.; Nowakowski, Sara; Tal, Joshua Z.; Grandner, Michael A.
Intimate partner violence (IPV) is a worldwide health concern and an important risk factor for poor mental/physical health in both women and men. Little is known about whether IPV leads to sleep disturbance. However, sleep problems may be common in the context of IPV and may mediate relationships with mental/physical health. Data from the 2006 Behavioral Risk Factor Surveillance System (BRFSS) were used ( N = 34, 975). IPV was assessed in female and male participants for any history of being threatened by, physically hurt by, or forced to have sex with an intimate partner (THREAT, HURT, and SEX, respectively), and, further, as being forced to have sex with or physically injured by an intimate partner within the past year (SEXyr and HURTyr, respectively). These survey items were coded yes/no. Sleep disturbance was assessed as difficulty falling asleep, staying asleep, or sleeping too much at least 6 of the last 14 days. Logistic regression analyses, adjusted for age, sex, race, income, education, and physical/mental health, assessed whether IPV predicted sleep disturbance. Sobel–Goodman tests assessed whether relationships between IPV and physical/mental health were partially mediated by sleep disturbance. All IPV variables were associated with sleep disturbance, even after adjusting for the effects of age, sex, race/ethnicity, income, education, employment, marital status, physical health and mental health. THREAT was associated with sleep disturbance (odds ratio [OR] = 2.798, p < .0001), as was HURT (OR = 2.683, p < .0001), SEX (OR = 3.237, p < .0001), SEXyr (OR = 7.741, p < .0001), and HURTyr (OR = 7.497, p < .0001). In mediation analyses, all IPV variables were associated with mental health ( p < .0001), and all were associated with physical health ( p < .007) except SEXyr. Sleep disturbance partially mediated all relationships (Sobel p < .0005 for all tests). Mediation was around 30%, ranging from 18% (HURTyr and mental health) to 41% (HURT and physical health). IPV was strongly associated with current sleep disturbance above the effect of demographics and overall mental/physical health, even if the IPV happened in the past. Furthermore, sleep disturbance partially mediates the relationship between IPV and mental/physical health. Sleep interventions may potentially mitigate negative effects of IPV.